Comparison of Membrane‐Permeant Fluorescent Probes for Sperm Viability Assessment in the Ram. Issue 4 (7th January 2013) - Yániz, JL; Palacín, I; Vicente‐Fiel, S; Gosalvez, J; López‐Fernández, C; Santolaria, P
Contents This study was designed to compare the effectiveness and usability of four permeant fluorochromes (CFDA; SYBR‐14; Hoechst‐33342; and acridine orange), combined with propidium iodide to assess sperm membrane integrity. Three different experiments were conducted. The first trial was designed to study the optimal dye concentration and minimum incubation time required to achieve optimum fluorescence intensities and contrast for each fluorochrome combination using ram fresh semen samples. Both SYBR‐14 and acridine orange allowed a direct assessment of sperm membrane integrity, without the need of incubating samples, whereas a minimum of 4 and 6 min of incubation at 37°C was necessary to achieve optimum fluorescence intensities in the CFDA and Hoechst groups, respectively. In the second trial, fresh semen samples were mixed with different volumes of membrane‐affected sperm (semen treated with three cycles of freezing to −20°C and thawing at room temperature) to produce semen samples with known proportions of damaged spermatozoa. The results were compared with the theoretical values predicted on the basis of the estimations made on fresh and frozen samples. The proportions of damaged sperm in each sample determined using the four fluorochrome combinations agreed with the predicted theoretical values, with the acridine orange/propidium iodide providing the best adjustment. The third experiment was performed to compare the results of sperm membrane integrity using the four fluorochrome combinations. The proportions of plasmalemma‐intact sperm determined by acridine orange and SYBR‐14 were greater (p < 0.0001) than the proportions of intact sperm determined by CFDA and Hoechst stains. It was concluded that the most efficient combinations to be used in ram sperm were AO/PI and SYBR/PI because it allowed a direct assessment of sperm viability without the need to incubate samples and obtaining reliable results.